Liberty, Equality, Power : A History of The American People - Murrin, John M. [et al.] (Australia Thomson/Wadsworth, 2005)
Offers students an understanding of how America transformed itself, in a relatively short time, from a land inhabited by hunter-gatherer and agricultural Native American societies into the powerful industrial nation on earth. This title helps students understand the impact of the notions of liberty and equality.
Include Index and Illustration
Keywords: United States -- Study skills